(untitled) (Revista Innova Educación, 2023)
This research work presents the proposal of a technopedagogical intervention strategy aimed at promoting algorithmic thinking. The construct of algorithmic thinking is defined, and the selected technopedagogical strategy is described, which involves the use of the Scratch programming environment to develop algorithmic thinking through an electronic platform. The research was conducted using a quantitative, cross-sectional, and descriptive approach with a pretest-posttest design for a group of 48 students majoring in Computer Systems Administration at the University of Veracruz who were taking the educational experience in Algorithm Design and Implementation. The Wilcoxon test for related samples in SPSS was used to accept or reject the research hypothesis, which allowed for the observation of favorable results in the posttest compared to the pretest, concluding that the use of Scratch contributes to algorithmic thinking skills.